2017
DOI: 10.1016/j.immuni.2017.07.018
|View full text |Cite
|
Sign up to set email alerts
|

A Liver Capsular Network of Monocyte-Derived Macrophages Restricts Hepatic Dissemination of Intraperitoneal Bacteria by Neutrophil Recruitment

Abstract: The liver is positioned at the interface between two routes traversed by pathogens in disseminating infection. Whereas blood-borne pathogens are efficiently cleared in hepatic sinusoids by Kupffer cells (KCs), it is unknown how the liver prevents dissemination of peritoneal pathogens accessing its outer membrane. We report here that the hepatic capsule harbors a contiguous cellular network of liver-resident macrophages phenotypically distinct from KCs. These liver capsular macrophages (LCMs) were replenished i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
189
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 193 publications
(204 citation statements)
references
References 54 publications
12
189
0
3
Order By: Relevance
“…However, it has to be kept in mind that the hepatic capsule harbors a unique cellular network of macrophages phenotypically distinct from KCs that restricts the hepatic dissemination of intraperitoneal bacteria. (70)…”
Section: Peritoneal Macrophagesmentioning
confidence: 99%
“…However, it has to be kept in mind that the hepatic capsule harbors a unique cellular network of macrophages phenotypically distinct from KCs that restricts the hepatic dissemination of intraperitoneal bacteria. (70)…”
Section: Peritoneal Macrophagesmentioning
confidence: 99%
“…(19) These data suggest that tissue repair Ly-6C Low/monocytes contribute to the resolution of CF. A recent study identified F4/80 + capsular macrophages beneath the liver surface, (29) but the F4/80monocytes we analyzed appear to be different cell types.…”
Section: Discussionmentioning
confidence: 64%
“…Twenty‐two years later, Tadeusz Browicz correctly identified them as a large population of liver‐resident macrophages. KCs are widely distributed within the liver, but they are not evenly spread . KCs are usually present in areas away from larger vessels, and they exclusively inhabit the sinusoidal intravascular compartment and are anchored to the liver sinusoidal endothelial cells (LSECs).…”
Section: Myeloid Lineagementioning
confidence: 99%
“…However, CX3CR1 marker is expressed on DCs, but not on mature KCs under homeostatic conditions, making this chemokine receptor useful for identification of DCs both in vivo and in vitro. However, a recent publication has challenged this concept suggesting that CX3CR1+ cells that reside underneath the liver capsule are a population of macrophages . Functional assays and specific CX3CR1‐mediated cell depletion will be crucial to further determine the exact function of these cells.…”
Section: Myeloid Lineagementioning
confidence: 99%
See 1 more Smart Citation